Age-Related Macular Degeneration - Therapies and Their Delivery - Ponnusamy, Chandrasekar; Ayarivan, Puratchikody; Selvamuthu, Preethi; Natesan, Subramanian (Current Drug Delivery, 2024)
Age-related macular degeneration (ARMD) is a degenerative ocular disease that is the most important cause of irreversible vision loss in old-aged people in developed countries. Around fifty percent of vision impairments in developed countries are due to ARMD. It is a multifaceted disease that is associated with both genetic and environmental risk factors. The most important treatments option for ARMD includes laser photocoagulation, photodynamic therapy (PDT), Anti-VEGF Injections, and combination therapies. In this review, we also propose that topical ocular drug delivery with nanocarriers has more attention for the treatment of ARMD. The nanocarriers were specially designed for enhanced corneal residential time, prolonged drug release and action, and minimizing the frequency of administrations. Different types of nanocarriers were developed for the topical ocular delivery system, such as nanomicelles, nanoemulsions, nanosuspensions, liposomes, and polymeric nanoparticles. These topical ocular nanocarriers were administered topically, and they can fix the hydrophobic substances, increase solubility and improve the bioavailability of an administered drug. Hence the topical ocular delivery systems with nanocarriers provide a safe and effective therapeutic strategy and promising tool for the treatment of posterior segment ocular diseases ARMD.
Keywords: common ocular diseases